Pengaruh Model Pembelajaran Auditory Intelektually Repertition Terhadap Kemampuan Komunikasi Matematis Siswa Kelas X SMAN 14 Padang - Mutiara, Nurul; Rahmalina, Widdya; Mulyati, Asrina (UNIVERSITAS SERAMBI MEKKAH, 2025)
This research is motivated by the weak mathematical communication skills of students in participating in mathematics learning. It is known that during the learning process, students are unable to express their opinions, and their mathematical communication skills are weak, requiring appropriate learning models to improve students' mathematical communication skills in mathematics learning. This study aims to determine the effect of the auditory intellectual repetition learning model on students' mathematical communication skills in mathematics, particularly in the statistics material in class X SMAN 14 Padang. The type of research is Quasi Experiment (quasi-experiment), and the research design used is Nonequivalent Control Group Design. The experimental class was treated using the auditory intellectual repetition learning model, while the control class used conventional methods. Based on the research results, the Mann Whitney U test analysis showed a value of 0.001 < 0.005. Therefore, it can be concluded that H0 is rejected and H1 is accepted, which reads “there is a significant influence of the learning model on students' mathematical communication skills in mathematics subjects in statistics material in class X SMAN 14 Padang.”